Moral Education in the Family and the Phenomenon of Infidelity - Mahmud, Salami; Sakdiah; Fatmawati; Mashuri; Furqan, Muhammad (Pascasarjana Universitas KH. Abdul Chalim, 2024)
Moral education is the fundamental basis for developing an individual's character, commencing within the immediate social context, specifically the family unit. The role of families in creating moral and ethical ideals that will serve as guiding principles for individuals in their daily lives is of the greatest significance. The absence of moral education contributes to the increasing rate of infidelity within current society. This article aims to highlight various factors influencing moral education within the family and explore their connection to the tendency to commit infidelity. This research uses an extensive literature review to collect data from various sources. Researchers analyzed research, books, and articles on moral education in the family and infidelity and looked for relevant findings. The results show that self-preservation morals play a crucial role in preventing infidelity. A case of infidelity behavior is frequently associated with a consistent pattern of moral values instilled by parents, whereby those who have been raised in an environment characterized by honesty, responsibility and love, tend to exhibit similar actions after getting married. A responsible person undertakes parental duties by demonstrating affection for his spouse, like he loves his mother or sister, thereby preventing infidelity.